On the flow structure and control efficiency of rudder surround curved-wall subject to high-energy jet array: A numerical study - Zhou, Yi; Luo, Zhenbing; Liu, Qiang; Zhou, Yan; Xie, Wei (Physics of fluids (1994), 2025)
The flight of a Cross-Domain High-Speed Vehicle (CDHSV) is characterized by substantial variations in both speed and altitude. Traditional mechanical rudder-based attitude control of CDHSVs suffers from several limitations, such as reduced control efficiency and diminished sensitivity to changes in rudder rotation angle. To address these challenges, this paper proposes the integration of a high-energy jet array downstream of the rudder. This arrangement aims to modify the flow field structure in the curved-wall rudder region, thereby enhancing the rudder's control efficiency. The study investigates the impact of different high-energy jet array configurations on the flow field structure within the curved-wall rudder region, focusing on flight altitudes ranging from 30 to 35 km and Mach numbers between 3 and 6. A comparative analysis is conducted to evaluate the control effects of the high-energy jet arrays across four distinct cases. The results indicate that the downstream high-energy jet array can significantly improve the control efficiency of the CDHSV's rudder in the curved-wall rudder flow field. This research provides valuable insights and a potential reference for enhancing rudder control efficiency in CDHSVs.